2015
DOI: 10.1590/0001-3765201420130262
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral alterations and Fos protein immunoreactivity in brain regions of bile duct-ligated cirrhotic rats

Abstract: Hepatic encephalopathy (HE) encompasses a variety of neuropsychiatric symptoms, including anxiety and psychomotor dysfunction. Although HE is a frequent complication of liver cirrhosis, the neurobiological substrates responsible for its clinical manifestations are largely unclear. In the present study, male Wistar rats were bile duct-ligated (BDL), a procedure which induces liver cirrhosis, and on the 21 st day after surgery tested in the elevated plus-maze (EPM) and in an open field for anxiety and locomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…For example, stimulation of E36 activated the limbic system (Hui et al 2005) and F3 caused limbic-cortical deactivation (Fang et al 2007). Moreover, the HPA axis activity was altered by EEA (Xu et al 2004, Sun and Wang 2007, Zhu et al 2015, Le et al 2015. It has been suggested that the ability of one particular stimulus 1010 RICARDO M. BASSETTO et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, stimulation of E36 activated the limbic system (Hui et al 2005) and F3 caused limbic-cortical deactivation (Fang et al 2007). Moreover, the HPA axis activity was altered by EEA (Xu et al 2004, Sun and Wang 2007, Zhu et al 2015, Le et al 2015. It has been suggested that the ability of one particular stimulus 1010 RICARDO M. BASSETTO et al…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral tests did not interfere in the immunohistochemical analyzes, because the peak of the expression immunoreactivity Fos protein in response to a stimulus occurs in about 40 to 60 min (Cespedes et al 2010, Le Sueur-Maluf et al 2015.…”
Section: Elevated Plus-maze (Epm) Testmentioning
confidence: 99%
“…All surgical procedures were performed under inhalational anesthesia involving 1.5% isoflurane (Baxter, São Paulo, SP, Brazil), nitrous oxide (0.8 L/min), and oxygen (0.4 L/min) with clean surgical techniques as previously described [ 65 ]. Briefly, obstructive jaundice was induced by midline laparotomy and common bile duct exposure followed by double ligation and section between stitches.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were submitted to a bile-duct ligation surgery as previously described. [10] Sham-animals were subjected to the same surgical procedure, except the bile duct was not ligated.…”
Section: Bile-duct Ligationmentioning
confidence: 99%